ANALISIS ASPEK GRAMATIKAL DAN ASPEK LEKSIKAL PUISI “PAPUA” KARYA FRANS P. PANDONI - Sitti Mariati (Balai Bahasa Provinsi Papua, 2019)
Poetry as a discourse is arranged by grammatical and lexical aspects. Therefore, to know what grammatical and lexical aspects are used by the author in writing the poem